Pemanfaatan Jamur Trichoderma sp Sebagai Antagonis Patogen Busuk Sulur Tanaman Buah Naga Merah (Hylocereus polyrhizus) Secara In Vitro - Herlyan Prasetiyo; Purwati Purwati; Iin Arsensi (Universitas Widya Gama Mahakam, 2018)
Utilization of Trichoderma sp fungi as pathogenic fungi antagonists in red dragon fruit plants (Hylocereus polyrhizus) in vitro. The purpose of this study was to identify foul pathogens of dragon fruit plants and then test the ability of Trichoderma sp antagonists to deciduous pathogens of red dragon fruit plants in vitro. The study was conducted from August to October 2016, The research was conducted at the Laboratory of Pest and Plant Disease Sciences, Faculty of Agriculture, Mulawarman University, Samarinda. Sampling of plants exposed to foul tendrils was carried out in Bukit Merdeka Village, Samboja District, Kutai Kartanegara Regency. There are two data observed in this study, primary data and secondary data. Primary data is data obtained directly from the source through direct field observations and laboratory observations and secondary data data obtained from interviews with farmers. The results showed that the pathogen that causes tendon rot in dragon fruit plants is the fungus Colletotrichum gloesporioides (penz. Ssaac). Trichoderma sp can inhibit the development of pathogens Colletotrichum gloesporioides (Penz.) Ssaac., With the highest average resistance of 71.85%.